Organic agriculture: an empowering development strategy for small-scale farmers? A Cambodian case study : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Beban, Alice (Massey University, 2008)
This thesis explores claims that organic agriculture may be an empowering development strategy by investigating the impacts of conversion to organic farming systems on the lives of small-scale farmers in Cambodia. The thesis interrogates the diverse uses and abuses of the term =empowerment‘ in development rhetoric and argues for an empowerment model that is derived from farmers‘ self-defined concepts of development. This model was used to conduct a qualitative case study involving semistructured interviews and focus groups with members of organics initiatives in seven diverse Cambodian communities. Results indicate that many farmers in all communities felt that their most important objective was not only to achieve food security, but to be able to grow sufficient rice to feed their family. Farmers joined the organics initiatives primarily to improve their health and reduce the cost of farming inputs. As a result of joining the initiatives, all farmers (including both certified and non-certified organic farmers) felt they had improved their health and food security. Most farmers also increased incomes, created stronger family and community ties and felt they had more control over their livelihoods. These benefits were not, however, distributed equally amongst individuals or communities. Very poor and isolated farmers could not generally access benefits. The three main factors that determined the impact of the organics initiatives on farmer empowerment were identified as: the individual‘s level of resources, the strength of the farmer group, and the policies and values of the supporting organisation. The implications for future initiatives are, firstly, the tremendous potential for farmers and wider rural communities to benefit from organic agriculture as a development strategy. However, this study also shows that if organics is to be viable for low-resource people, it may be necessary to promote both resources and techniques in organics initiatives. Also, a focus on building strong relationships both within the farmers group and linkages with local and wider stakeholders may enhance long-term sustainability of organics initiatives.
Keywords: Organic farming; Empowerment; Development strategy; Development initiatives; Fields of Research::340000 Economics::340200 Applied Economics::340213 Economic development and growth